Measurement of renal cortex perfusion: A direct comparison of arterial spin labelling magnetic resonance imaging and 15OH2O positron emission tomography - Olsen, Naja Enevold; Mariager, Christian Østergaard; Arildsen, Maibritt Meldgaard; Nielsen, Sebastian; Vendelbo, Mikkel Holm; Pedersen, Michael; Laustsen, Christoffer; Ringgaard, Steffen; Tolbod, Lars Poulsen; Buus, Niels Henrik (Magnetic resonance in medicine, 2025)
Reliable information about renal blood supply is important to understand kidney physiology and diseases. Arterial spin labeling MR (ASL-MR) imaging and [15O]H2O positron emission tomography (PET) can noninvasively measure tissue perfusion but have never been directly compared. Using a hybrid PET/MR scanner, we performed simultaneous cortex perfusion measurements to assess repeatability and reproducibility of both modalities and establish their mutual correlation.PURPOSEReliable information about renal blood supply is important to understand kidney physiology and diseases. Arterial spin labeling MR (ASL-MR) imaging and [15O]H2O positron emission tomography (PET) can noninvasively measure tissue perfusion but have never been directly compared. Using a hybrid PET/MR scanner, we performed simultaneous cortex perfusion measurements to assess repeatability and reproducibility of both modalities and establish their mutual correlation.Ten healthy subjects (mean 25 years, 5 males) with normal glomerular filtration rate were examined twice, 16 days (range 12-23) apart. Repeatability was assessed on Day 1 with two successive examinations. A single scan on Day 2 was used to assess reproducibility.METHODSTen healthy subjects (mean 25 years, 5 males) with normal glomerular filtration rate were examined twice, 16 days (range 12-23) apart. Repeatability was assessed on Day 1 with two successive examinations. A single scan on Day 2 was used to assess reproducibility.Single-kidney perfusion varied between individuals from 150 to 422 mL/min/100 mL for ASL-MR and from 184 to 470 mL/min/100 mL for PET. Repeatability and reproducibility were comparable between ASL-MR and PET. Bias was generally low (-13 to 5 mL/min/100 mL), but 95% limits of agreement (LoAs) were wide, ranging from 69 to 88 mL/min/100 mL. Overall, correlations between ASL-MR and PET perfusion values were weak, and in a linear mixed-effects model, bias was 18 and LoA 136 mL/min/100 mL. Agreement between ASL-MR and PET was acceptable at perfusion values between approximately 250 and 350 mL/min/100 mL. At lower perfusion, PET exceeded ASL-MR, whereas the opposite was observed at higher perfusion.RESULTSSingle-kidney perfusion varied between individuals from 150 to 422 mL/min/100 mL for ASL-MR and from 184 to 470 mL/min/100 mL for PET. Repeatability and reproducibility were comparable between ASL-MR and PET. Bias was generally low (-13 to 5 mL/min/100 mL), but 95% limits of agreement (LoAs) were wide, ranging from 69 to 88 mL/min/100 mL. Overall, correlations between ASL-MR and PET perfusion values were weak, and in a linear mixed-effects model, bias was 18 and LoA 136 mL/min/100 mL. Agreement between ASL-MR and PET was acceptable at perfusion values between approximately 250 and 350 mL/min/100 mL. At lower perfusion, PET exceeded ASL-MR, whereas the opposite was observed at higher perfusion.ASL-MR and [15O]H2O PET renal cortical perfusion show comparable repeatability and reproducibility. Although perfusion obtained with the two modalities overall correlate weakly, there is an acceptable agreement in the mid-physiological range.CONCLUSIONASL-MR and [15O]H2O PET renal cortical perfusion show comparable repeatability and reproducibility. Although perfusion obtained with the two modalities overall correlate weakly, there is an acceptable agreement in the mid-physiological range.